Pohutu Molo’opu: Ritual Penerimaan Pemimpin Baru di Gorontalo - Laya, Rachmi (Jurnal Bahasa, Sastra, dan Budaya, 2025)
One of the oral literature which is still used in Gorontalo customary event is Tuja'i Molo'opu. Oral literature is uttered at the ceremonial of officials reception in Gorontalo. As other traditions are changing. Tuja'i Molo'opu also along with the changes of the society. Therefore it needs to be held as the Foundation for preservation of the study of oral literature Tuja'i Molo'opu. This study aims to examines the performance of Molo'opu ceremonies. The theory used in this research is the theory of orality Albert Bates Lord and Ruth Finnegan. To apply this theory used Ethnographic aproaches. The ethnographic approach is used to explore data on performance as the cultural aspects of the community of Gorontalo. Data collected by documentation, recording, interview and observation. The results of this research show that aspects of orality in this tuja'i Molo'opu covering performance, which has several elements, namely: 1) ceremonial places and situations, 2) performers, 3) audiences and partisans (people involved in the ceremony), 4) media (facilities and infrastructure used both verbally and material), 5) customary attributes (which includes all the tools used in the traditional ceremony), 6) variations caused by the audience or other elements.